Study the Effect of Addition of Some Oxides on the Mechanical properties on Unsaturated Polyester Resin Compsites - Watan, Anaam W. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study included preparation for the unsaturated polyester samples before and after reinforced by Alumina oxide powder and copper oxide powder of different volume fraction amounting (3%,5%,8%). And this reearch included study of some of mechanical properties such as (hardness,compressive and wear).The results showed that increase of the hardness and compressive strength after the reinforced and increase with the volume fraction increase.As the wear test show that the wear rate increases with applied load from the different load(5,10,15)N,and the wear rate decreases with the volume fraction increase.